CHARACTERISTICS OF COASTAL ENVIRONMENT COMMUNITIES NEAR MANGROVE FOREST AREA IN KETAPANG PESAWARAN - Nugraheni, Irma Lusi; Saputra, Zikri; Safira, Anisa Fani (Politeknik Kelautan dan Perikanan Dumai, 2024)
The potential and uniqueness natural resources in coastal areas mangrove forest areas have a significant role in the economic, social, cultural and environmental development coastal communities. This research is a case study with qualitative and descriptive methods. The purpose this study is to provide an overview characteristics coastal communities in mangrove forest area in Ketapang, Teluk Pandan District, Pesawaran Regency. Research was carried out in June-July 2021. Scope the material in this study is characteristics coastal environment Ketapang Village which includes education level and livelihood. While the scope area in this study is the Ketapang Mangrove Forest Area. Used is secondary data obtained indirectly from the study literature on documents related to object research at several related agencies. The description, characteristics coastal community in the Ketapang mangrove forest area is aimed at interaction with the natural surroundings and community's desire to maintain and preserve the coastal environment mangrove forest area.